2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944389
|View full text |Cite
|
Sign up to set email alerts
|

Synergy analysis as a tool to design and assess an effective stroke rehabilitation

Abstract: Abstract-The poor rehabilitation success rate, including the cases of ineffective and detrimental adaptations, make stroke a leading cause of disability. Thus, it is essential to recognize the mechanisms driving healthy motor recovery to improve such rate. Stroke alters the Synergy Architecture (SA), the modular muscle control system. So SA analysis may constitute a powerful tool to design and assess rehabilitation procedures. However, current impairment scales do not consider the patient's neuromuscular state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Consequently, inappropriate muscle coordination [5] results in poor motor performance of the affected UL [17][18][19]. Due to their potential to convey information on the neurophysiology of the altered nervous system and subsequent motor impairment, different muscle synergy features have been proposed as quantitative biomarkers for UL motor function in stroke [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, inappropriate muscle coordination [5] results in poor motor performance of the affected UL [17][18][19]. Due to their potential to convey information on the neurophysiology of the altered nervous system and subsequent motor impairment, different muscle synergy features have been proposed as quantitative biomarkers for UL motor function in stroke [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of authors have investigated the neurological effects of VF [11,12], to our best knowledge the impact of VF in the control structure has not been addressed yet. In a preliminary study conducted on two simple upper-limb movements, we demonstrated that VF enhances the inter-limb similarity of the control structure [13]. Here, we have extended such study to the analysis of a complete upper-limb rehabilitation routine comprised of 12 movements.…”
Section: Introductionmentioning
confidence: 79%
“…Studies have shown that muscle synergies were robust across healthy subjects (3234). Thus, we adopted the synergy extracted from dominant arms of the control group as an efficient baseline of synergy (54, 55) and compared synergy of the affected arm in patients to the baseline synergy. In our study, synergy baseline extracted from healthy control group presented similar muscle activations with previous studies (28, 32).…”
Section: Discussionmentioning
confidence: 99%